Nurchayati - Rahma Nugroho; Safri Safri; Sofiana Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Health problems can be to every body, often health problems one of them is dyspepsia. Dyspepsia is term used on syndrome or set of syndrome consisting of pain or unconfertable at epigastrium, nausea, vomiting, bloating, full fast, full taste, and burp. This research purpose to know descpription of patient characteristic of patient with dyspepsia syndrome at Puskesmas Rumbai. Design of research used is descriptive. Sample in this reserch is 52 patient used technique purposive sampling. Equipment to take data used is questioner who done validation test and reliabilitation. Analysis data used is univariate. Result of research show 25-36 years old (38,5%), women, ethnic Minang (44,2%), and job as house wife (61,5%), smoker most unsmoker (59,6%), eat shape unmeasured (82,7%), while type of food and drink iritative (94,2%). It recommended for healthed provider in Rumbai to give counseling about dyspepsia, so that patient known have increase and can avert arise dyspepsia on patient. Keywords: Age, diet, dyspepsia, ethnicity, occupation